IJCM_168A: Cardiovascular disorder risk among the police personnel in Ernakulam District, Kerala, India - Shaji Shibin M; Aswathy S (Wolters Kluwer Medknow Publications, 2024)
Background: Appropriate assessment and management of cardiovascular risk is vital in reducing the occurrence of fatal and non fatal cardiovascular events like stroke or myocardial infarction in high risk occupational group such as Police personnel. Several studies have reported high prevalence of risk factors of cardiovascular diseases (CVD) such as hypertension, high blood lipids, physical inactivity, obesity, positive family history etc among police personnel Objective: To estimate the 10-year risk of cardiovascular events (fatal or non-fatal) among police personnel in Ernakulam City, Kerala, India Methodology: A cross sectional study was carried out among police personnel in various police stations of the district. All the police stations in the district were listed and selected randomly using the MS Excel random number generator. After getting prior permission from the concerned authorities in the Police department, Police personnel above the age of 40 years in Ernakulam city were screened for CVD risk using the WHO - non-laboratory-based CVD risk chart. Data was entered into Microsoft Office Excel and analysed using Jamovi version 2.3.28 Results: Out of 246 participants studied, the mean age was 48.4 + 3.97. Less than half of the participants (44.3%) were Civil Police Officers (CPO) or Senior Civil Police Officer (SCPO). About a third of the participants (32.1%) were having CVD risk in yellow category (5-<10%), 3.3% in orange category (10-<20%) and majority (64.6%) in green category (<5%). On multivariate analysis, age>50 years (OR - 3.36[1.73,6.5]) and duration of service>20 years (OR - 4.9[2.35,10.23] were the independent determinants of higher CVD risk (yellow and orange category) Conclusion: About 35% of the participants belonged to higher risk category (yellow and orange) and duration of service>20 years, age>50 years were the independent determinants